Meeting the challenges posed by an escalating diabetes healthcare burden: A mixed methods study. Issue 6 (2nd November 2019) - Atsalos, Christine; Payk, Marlene; O'Neill, Ann; Inglis, Sally; Cheung, N. Wah; Jackson, Debra
Abstract : Background: The ongoing escalation in the incidence of diabetes is contributing to a growing burden on health services because patients with diabetes as a co-morbidity are now spread throughout the hospital (rather than being located in specific areas). Thus, there is a need for expertise in diabetes care throughout services to ensure optimal care and reduce threats to patient safety. Aims and objectives: To identify new strategies to maintain optimal care for patients with diabetes while in hospital. Design: Mixed methods underpinned by Appreciative Inquiry. Methods: The Diabetes Knowledge Questionnaire Survey (DKQS) ( n  = 173); focus group interviews with nurses and midwives ( n  = 40), and individual interviews with recently discharged hospital patients ( n  = 6). Quantitative data were analysed using descriptive statistics and qualitative data by thematic analysis. Results: Highlight a need to enhance knowledge and confidence of diabetes management among nursing, midwifery, medical and ancillary staff through the introduction of focused education strategies. This, together with improved communication and team work, is required to relieve the burdens on frontline nursing staff and patients caused by delays in prescribing and reviewing insulin requirements and in accessing needed food for people with diabetes. Conclusions: In seeking solutions to the challenges in caring for hospitalised patients with diabetes there is a need to work across the entire hospital workforce and to develop effective and efficient methods for ensuring appropriate skills and knowledge of diabetes management for staff across complex and rapidly changing hospital systems. Relevance to clinical practice: The introduction and implementation of innovative educational and organisational strategies are needed to assist in meeting the challenges posed by an escalating diabetes healthcare burden. The safety of patients with diabetes can be optimised with the timely availability of appropriate meals and snacks, and enhanced coordination and communication between and within multidisciplinary teams.